JURIDICAL CHARACTER OF UNCERTIFICATED SECURITIES <file:///D:\Documents%20and%20Settings\!!!\Local%20Settings\Temp\Word_0> - D. V. Lubyagina; N. A. Abuzyarova (Russian Journal of Economics and Law)
The article views the issues of the juridical character of uncertificated securities . The existing scientific viewpoints on the problem of the property and liability correlation in a security are analyzed. The author justifies the necessity to confirm the institute of uncertificated securities not in the traditional norms, referring to the material objects turnover, but in the special norms.